The development of instruments for farmers’ participation in water management in tidal lowlands using confirmatory factor analysis - Tafarini, Meitry Firdha; Yazid, Muhammad; Suryadi, F.X.; Prayitno, Bambang; Faizal, Muhammad; Khairul Fahmi Purba, Khairul (Emirates Journal of Food and Agriculture, 2022)
Water user associations or farmer groups carry out water management on tidal land. In its management, the participation of farmers in the group is necessary. This study aimed to examine the indicators of participation that positively affect the sustainability of tidal agriculture. The variables used in this study are participation (5 indicators), leadership (5 indicators), attitude & understanding (4 indicators), and utilization & maintenance (4 indicators). The research locations were in the tidal area of Telang Karya and Telang Rejo Village. The number of samples in this study was 245 farmers. This study used confirmatory factor analysis (CFA) by building the model of first-order CFA and second-order CFA. Evaluation of the model was done by looking at the Goodness of Fit Indexes, namely chi-square (χ2), root mean square error of approximation (RMSEA), CFI, TLI, GFI, and AGFI. The research results on the second-order CFA resulted in a value of R2 = 137.414, and the model was a good fit. The results of the indicators analysis used were significant to be applied in tidal lowlands agriculture.